Needs and preferences for nutrition education of type 2 diabetic adults in a resource-limited setting in South Africa - Jane W. Muchiri; Gerda J. Gericke; Paul Rheeder (AOSIS, 2012)
Diabetes self-management education is crucial in diabetes care. Education that is tailored to the needs of the patient is considered the most effective in improving health outcomes. Diet, a critical element of diabetes treatment, is reported as the most difficult to adhere to by both patients and health professionals. Tailored nutrition education (NE) could benefit diabetic individuals with low socio-economic status, who are amongst those noted to have poor health outcomes. This qualitative interpretive phenomenological study aimed to explore and describe the NE needs of adults with type 2 diabetes mellitus to guide development of a tailored NE programme for resource-poor settings. Participants were 31 non-insulin-dependent type 2 diabetic patients (convenience sample) and 10 health professionals. Focus group discussions using semi-structured questions were held with the diabetics, and open-ended self-administered questionnaires were used with the health professionals. Data analysis was done using Krueger's framework approach. Disease-related knowledge deficits and inappropriate self-reported dietary practices, including intake of unbalanced meals, problems with food portion control and unsatisfactory intake of fruits and vegetables, were observed. Recommendations for the NE programme included topics related to the disease and others related to diet. Group education at the clinic, a competent educator and comprehensive education were indicated by the patients. Participation of family and provision of pamphlets were aspects recommended by patients and health professionals. Barriers that could impact the NE included financial constraints, food insecurity, conflict in family meal arrangements and access to appropriate foods. Support from family and health professionals and empowerment through education were identified as facilitators to following dietary recommendations by both groups of participants. Knowledge deficits, inappropriate dietary practices and barriers are issues that need addressing in an NE programme, whilst the suggestions for an NE programme and facilitators to dietary compliance need to be incorporated.Onderrig in die selfbestuur van diabetes is essensieel in diabetessorg. Onderrig wat spesifiek ooreenkomstig die behoeftes van die pasiënt aangepas is, word die mees doeltreffend in die verbetering van gesondheiduitkomste geag. Dieet, 'n kritiese element in diabetesbehandeling, word deur pasiënte en gesondheidpraktisyns as die moeilikste beskou om na te volg. Spesifiek beplande voedingonderrig kan tot voordeel van lae sosio-ekonomiese diabete wees wat deel van diegene wat swak gesondheiduitkomste toon, uitmaak. Die doel van hierdie kwalitatiewe interpreterende fenomologiese studie was om die voedingonderrigbehoeftes van volwassenes met tipe 2 diabetes mellitus te ondersoek en te beskryf ten einde die ontwikkeling van 'n voedingonderrigprogram wat op hulpbrondbeperkte omgewings afgestem is, te rig. Een en dertig nie-insulien afhanklike tipe 2 diabetes pasiënte (geriefsteekproef) en 10 gesondheidpraktisyns was evalueer. Fokusgroepbesprekings deur gebruikmaking van semi-gestruktureerde vrae, is met die diabete gehou. Self-geadministreerde oop-eindigende vraelyste is deur die gesondheidpraktisyns voltooi. Data-analise is volgens Krueger se raamwerkbenadering gedoen. Siekteverwante kennisgapings en ontoepaslike self-gerapporteerde dieetpraktyke, insluitend ongebalanseerde maaltye, probleme met porsiekontrole en ontoereikende inname van groente en vrugte is gerapporteer. Aanbevelings vir die voedingonderrigprogram het onderwerpe verwant aan die siekte en die dieet ingesluit. Die pasiënte het groeponderrig by die kliniek, 'n bevoegde onderrigpraktisyn en omvattende onderrig verkies. Die pasiënte en die gesondheidpraktisyns het gesinsdeelname en die beskikbaarstelling van pamflette aanbeveel. Struikelblokke wat negatief op die voedingonderrigprogram kon inwerk, het finansiële beperkinge, voedselinsekuriteit, konflik met gesinsmaaltydreëlings en toegang tot geskikte voedsels ingesluit. Ondersteuning van die gesin en gesondheidpraktisyns, sowel as bemagtiging deur kennis is as fasiliteerders ter bevordering van die navolging van dieetaanbevelings deur beide groepe deelnemers geïdentifiseer. Tekortkominge in kennis, ontoepaslike dieetpraktyke en struikelblokke is aspekte wat in 'n voedingonderrigprogram aangespreek behoort te word. Voorstelle wat vir die voedingonderrigprogram en fasiliteerders gemaak is vir dieetnavolging, behoort in die program ingesluit te word.